Oral Corticosteroid Use and the Risk of Acute Myocardial Infarction in Chronic Obstructive Pulmonary Disease - Laetitia Huiart; Pierre Ernst; Xavier Ranouil; Samy Suissa (Canadian Respiratory Journal)
BACKGROUND: Given the limited efficacy of oral corticosteroids in treating chronic obstructive pulmonary disease (COPD), the possible cardiac side effects of oral corticosteroids are of particular concern in an elderly population. The impact of the use of oral corticosteroids on the risk of acute myocardial infarction (AMI) in a cohort of patients with COPD was studied.